2013
DOI: 10.1186/1471-2407-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Progress risk assessment of oral premalignant lesions with saliva miRNA analysis

Abstract: BackgroundOral cancer develops through multi-stages: from normal to mild (low grade) dysplasia (LGD), moderate dysplasia, and severe (high grade) dysplasia (HGD), to carcinoma in situ (CIS) and finally invasive oral squamous cell carcinomas (OSCC). Clinical and histological assessments are not reliable in predicting which precursor lesions will progress. The aim of this study was to assess the potential of a noninvasive approach to assess progress risk of oral precancerous lesions.MethodsWe first used microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 22 publications
2
50
0
5
Order By: Relevance
“…Yang et al identified 25 miRNAs differentially expressed between progressive and non-progressive low-grade oral dysplasia leucoplakia [150]. They went on to identify 5 of those to be detectably differentially expressed in the saliva of patients with progressive low-grade dysplasia compared to non-progressive.…”
Section: Precancermentioning
confidence: 98%
“…Yang et al identified 25 miRNAs differentially expressed between progressive and non-progressive low-grade oral dysplasia leucoplakia [150]. They went on to identify 5 of those to be detectably differentially expressed in the saliva of patients with progressive low-grade dysplasia compared to non-progressive.…”
Section: Precancermentioning
confidence: 98%
“…Furthermore, the roles of miRNAs have been described in several diseases, including cancers [70,71,72,73], coronary diseases [74,75,76], autoimmune diseases [77,78,79] or viral infections such as viral hepatitis [80,81,82,83]. miRNAs predominantly exist intracellularly, however, it is possible to find miRNAs in extracellular environments such as in serum, plasma, semen, cerebrospinal fluid and urine [84,85,86,87,88,89,90,91]. Two hypotheses are proposed to explain the origin of circulatory miRNAs.…”
Section: Circulatory Mirnas As Biomarkers Of Diseasementioning
confidence: 99%
“…In 2013, Yang et al . [72] reported firstly the use of microRNA microarray to profile low-grade dysplasia (LGD) oral premalignant lesions (OPLs) from progressing and non-progressing LGD OPLs, in order to explore the possible microRNAs, which later could lead the progression into high-grade dysplasia (HGD) or OSCC. They identified 25 miRNAs differentially expressed between progressive and non-progressive LGD leukoplakias.…”
Section: Salivary Non-coding Rnas Associated With (Patho) Physiolomentioning
confidence: 99%